Ray tracing model for long-range acoustic vortex wave propagation underwater - Kelly, Mark E.; Zou, Zheguang; Zhang, Likun; Shi, Chengzhi (Frontiers in Acoustics, 2023)
The use of vortex waves in multiple environments is of increasing interest for numerous applications including underwater acoustic communications, particle manipulations, and sonothrombolysis. Finite element methods are limited in the range for which the propagation of these vortex beams may be simulated. On the other hand, ray tracing programs simulate well over long ranges, though are generally limited in their ability to resolve the features of a propagating vortex.Methods for overcoming these difficulties in simulating the long-range propagation of such waves in inhomogeneous environments have been developed and employed, though their specific implementation has not been thoroughly discussed. This manuscript provides the methods by which existing ray tracing programs may be used to approximate the long-range propagation of acoustic vortex beams in complex environments.